Development of affordable rain gauge for rain rate and fade measurements - Chuah, Chong Hao (2024)
Rain rate and rain fade are important parameters that are used in the world of telecommunications. Rain rate and fade directly affect the signal strength and signal transmission of the communication systems. The rain fade is a useful parameter to observe signal loss on high frequency links due to rain. Rain rate is the key parameter to calculate rain fade. The measurement of rain rate is in the unit of millimeter per hour while the rain fade is in the unit of decibels per kilometer. The rain rate is usually determined by using a device called the rain gauge but current industrial grade instruments for measuring the rain rate are too expensive and not affordable. The data provided online is also inconsistent without frequent updates and require longer time to obtain them. The rain gauge available in the market also lacks the use of IoT, making obtaining the data to be in manual mode and require frequent human interaction with it. Hence, a low-cost microcontroller-based rain gauge that uses the tipping bucket mechanism is designed and developed in this project research. The rain gauge uses 3D printing materials, lowering the cost and also uses low-cost components to limit the total cost of the project. The electronic circuit of this project comprises of a Hall Effect Sensor, a ESP32 microcontroller, a real-time clock module and a MicroSD card module. The data is programmed to be stored in both Google Sheets and in MicroSD card as a backup at every 1 minute interval. The whole system is stored within a waterproof electrical junction box, sealed with silicone strip, providing an extra layer of waterproof to the circuit. The collected data is compared and analyse with reference to a nearby station that provides rainfall data and from the analysis, the difference is in an acceptable range.